Childhood and Adolescent Overweight, Obesity and Socio-Economic Circumstances in The Gulf Cooperation Council Countries: A Systematic Review - Almughamisi, Manal Amro; O’Keeffe, Majella; Harding, Seeromanie (Journal of medical and pharmaceutical sciences, 2023)
The Gulf Cooperation Council (GCC) Countries are high-income but, unlike those in Europe and North America, uncertainty exists about the patterning of childhood obesity by socio-economic circumstances (SEC). This paper systematically reviews the association between overweight or obesity and SEC in children and adolescents, aged 5-19 years, in the GCC countries. Between 2000 and May 2020, 785 papers were identified, 45 full-text articles were reviewed and ten papers of studies in Kingdom of Saudi Arabia (KSA), Bahrain, Kuwait and Qatar were included. Thirty-one SEC-overweight/obesity associations were examined with seven SEC indicators, with parental education and employment being commonly used indicators. Sixteen positive associations were reported in seven studies and two negative associations in two studies. Of the positive associations, eight were among girls, three among boys and five among girls and boys combined. Multivariable adjustments were conducted in three studies and showed that maternal employment was independently associated with just under a two-fold increase in overweight and obesity. The small available evidence base indicates that SEC was generally either positive, more so among girls than boys, or not associated with overweight and obesity among children and adolescents. These findings signaled the importance of rapidly transitioning contexts of the GCC countries on childhood and adolescent overweight and obesity.
Keywords: obesity; overweight; adolescents; socioeconomic